The politics of race : Canada, the United States, and Australia - Vickers, Jill, 1942-; Isaac, Annette, 1951- (University of Toronto Press, 2012)
As race and politics become increasingly intertwined in both academic and popular discourse, The Politics of Race aids readers in evaluating different approaches for promoting racial justice and transforming states.